Taxation and Corporate Governance - Siman, Ariel; Avi-Yonah, Reuven (Columbia Journal of Tax Law, 2024)
Legal and economic scholars have examined the intersection between corporate governance and taxation; however, recent legal scholarship has generally focused on the interplay between director compensation, management measures in the face of the market for corporate control, and the double taxation of inter-corporate dividends. Other aspects of the relationship between corporate governance and taxation have received limited attention. This article aims to fill this gap in the literature. First, this paper discusses the corporate agency problem and the existing justifications for the corporate tax. Second, this paper argues that the corporate tax can be justified on the ground that it mitigates the corporate agency problem more effectively and with fewer adverse consequences than alternative taxation systems.